First report of highly pathogenic Echinococcus granulosus genotype G1 in dogs in a European urban environment - Laurimaa, Leidi (Parasit Vectors, 2015)
BACKGROUND: Echinococcus granulosus and E. multilocularis are tapeworm parasites of major medical and veterinary importance, causing cystic and alveolar echinococcosis, respectively. Both diseases are listed among the most severe parasitic diseases in humans, representing 2 of the 17 neglected diseases prioritised by the World Health Organisation. However, little is known about the role of urban animals in transmission of both parasite species. FINDINGS: A sensitive non-invasive genetic method was used to monitor E. granulosus and E. multilocularis infection among dog faecal samples collected from an urban area in Estonia in 2012–13. Out of 181 dog faecal samples analysed, 2.2% tested positive for E. granulosus, determined by sequencing as genotype G1. None of the samples tested positive for E. multilocularis. CONCLUSIONS: We report contamination of an urban environment with highly pathogenic E. granulosus G1 disseminated by dogs, and a potential risk to human health.